Pengelolaan dan Pemanfaatan Koleksi Antiquariat di Perpustakaan Pusat Data dan Dokumentasi Ilmiah - Noorika Retno Widuri; Dwi Untari; Tupan Tupan (Media Pustakawan, 2022)
Antiquariat collections for taxonomic researchers are very vital collections because they are used to compare species found in the field. To fulfill this, the LIPI Scientific Data and Documentation Center conducted a survey on the use of antiquariat collections by researchers in the Cibinong area library, Purwodadi area library, Bogor-Cibodas area library, Ambon area library and Jakarta area library. The survey aims to (1) determine the utilization of antiquariat collections available in the library; (2) knowing the management of the types of antiquariat collections available in the library; (3) know the procedures for storing antiquariat collections. The survey was conducted on April 27 to May 31, 2021 using the google form. The survey results state that researchers need antiquariat collections as a source of reference and a source of knowledge in conducting research. The researcher supports the transfer of antiquariat collection media in digital form. The special room for the storage of antiquariat collections has not met the requirements, causing the collections to be easily fragile and damaged. The high intensity of use is one of the factors causing damage to the collection. Media transfer on antiquariat collections needs to be done immediately to prevent damage and facilitate its use by researchers. Based on the facts in the field and the results of the survey, it is recommended to prepare a special storage room for antiquariat collections, immediately carry out the transfer of antiquariat collection media, and procure collections or collaborate on the use of antiquariat collections.